Pengaruh Self Efficacy Terhadap Kinerja Karyawan Housekeeping Di Hotel Aryaduta Lippo Village : The Influence of Self-Efficacy on the Performance of Housekeeping Employees at the Aryaduta Lippo Village Hotel - farrah farrah; Ratih Dwi Astuti; Muhammad Aldi (Jurnal Bisnis dan Ekonomi, 2025)
This study investigates the effect of self-efficacy on the performance of housekeeping employees at Hotel Aryaduta Lippo Village. Self-efficacy is defined as an individual’s belief in their capability to perform specific tasks and handle challenges effectively. In the hotel industry, employee performance is crucial to operational success, particularly in the housekeeping department, which ensures cleanliness and comfort for guests. A quantitative research design with an associative approach was employed to examine the relationship between self-efficacy and employee performance. The population of this study consisted of all housekeeping staff at Hotel Aryaduta Lippo Village. Data were collected through questionnaires using a Likert scale and analyzed using simple linear regression to measure the influence of self-efficacy on performance. The results of the regression analysis show that the coefficient of the independent variable, self-efficacy (X), is 0.935 and has a positive value, indicating a significant and positive relationship with employee performance (Y). This finding demonstrates that higher levels of self-efficacy contribute to better performance among housekeeping employees. The study highlights the importance of enhancing self-efficacy as a strategy to improve employee outcomes and overall service quality in the hospitality industry.